Minimal English for a Global World Improved Communication Using Fewer Words (Springer International Publishing, 2018)
This book introduces a new tool for improving communication and promoting clearer thinking in a world where the use of Global English can create numerous comprehension and communication issues. Based on research findings from cross-linguistic semantics, it contains essays and studies by leading experts exploring the value and application of 'Minimal English' in various fields, including ethics, health, human rights discourse, education and international relations. In doing so, it provides informed guidelines and practical advice on how to communicate in clear and cross-translatable ways in Minimal English. This innovative edited collection will appeal to students and scholars of applied linguistics, language education and translation studies. Cliff Goddard is Professor of Linguistics at Griffith University, Australia, and a Fellow of the Australian Academy of the Humanities. His research interests lie at the intersection of language, meaning and culture. He has published widely in descriptive and theoretical semantics, language description and typology, ethnopragmatics and intercultural communication.